Late treatment of a mandibular gunshot wound - Yuri Slusarenko da Silva; Marcia Maria de Gouveia; Carlos Augusto Ferreira Alves; Rodrigo Chenu Migliolo (University of São Paulo, 2015)
Mandibular gunshot injuries are esthetically and functionally devastating, causing comminuted fractures and adjacent tissue destruction depending on the weapon gauge, projectile shape, impact kinetic energy, and density of the injured structures. If the mandibular fracture is not adequate or promptly treated, the broken fragments will fail to heal. In case of a treatment delay, progressive bone loss and fracture contracture will require a customized approach, which includes open reduction, removal of fibrous tissue between the bony stumps, and fixation of the fracture with a reconstruction plate and autogenous graft. The authors report the case of a 34-year-old man wounded on the mandible 15 years ago. With the aid of computed tomography and a prototype, a surgical plan was designed including open reduction and internal fixation of the segmental mandibular defect with a reconstruction plate and bone graft harvested from the iliac crest. The postoperative follow-up was uneventful and the 12-month follow up showed a positive aesthetic and functional result.